Establishing the scalable manufacture of primary human T‐cells in an automated stirred‐tank bioreactor. Issue 10 (9th July 2019) - Costariol, Elena; Rotondi, Marco; Amini, Arman; Hewitt, Christopher J.; Nienow, Alvin W.; Heathman, Thomas R.J.; Micheletti, Martina; Rafiq, Qasim A.
Abstract: Advanced cell and gene therapies such as chimeric antigen receptor T‐cell immunotherapies (CAR‐T), present a novel therapeutic modality for the treatment of acute and chronic conditions including acute lymphoblastic leukemia and non‐Hodgkin lymphoma. However, the development of such immunotherapies requires the manufacture of large numbers of T‐cells, which remains a major translational and commercial bottleneck due to the manual, small‐scale, and often static culturing systems used for their production. Such systems are used because there is an unsubstantiated concern that primary T‐cells are shear sensitive, or prefer static conditions, and therefore do not grow as effectively in more scalable, agitated systems, such as stirred‐tank bioreactors, as compared with T‐flasks and culture bags. In this study, we demonstrate that not only T‐cells can be cultivated in an automated stirred‐tank bioreactor system (ambr® 250), but that their growth is consistently and significantly better than that in T‐flask static culture, with equivalent cell quality. Moreover, we demonstrate that at progressively higher agitation rates over the range studied here, and thereby, higher specific power inputs (P/M W kg −1 ), the higher the final viable T‐cell density; that is, a cell density of 4.65 ± 0.24 × 10 6 viable cells ml −1 obtained at the highest P/M of 74 × 10 −4 W kg −1 in comparison with 0.91 ± 0.07 × 10 6 viable cells ml −1 at the lowest P/M of 3.1 × 10 −4 W kg −1 . We posit that this improvement is due to the inability at the lower agitation rates to effectively suspend the Dynabeads®, which are required to activate the T‐cells; and that contact between them is improved at the higher agitation rates. Importantly, from the data obtained, there is no indication that T‐cells prefer being grown under static conditions or are sensitive to fluid dynamic stresses within a stirred‐tank bioreactor system at the agitation speeds investigated. Indeed, the opposite has proven to be the case, whereby, the cells grow better under higher agitation speeds while maintaining their quality. This study is the first demonstration of primary T‐cell ex vivo manufacture activated by Dynabeads® in an automated stirred‐tank bioreactor system such as the ambr® 250 and the findings have the potential to be applied to multiple other cell candidates for advanced therapy applications. Abstract : This study focuses on the expansion of primary human T‐cells isolated from healthy donors in stirred tank bioreactors (ambr 250). Results show that higher stirring speed and higher specific power input do not have an impact on the final product composition and also lead to a higher final cell yield.